(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This article analyses the perspectives of educational management studies and the importance of leadership as an area of study. The article emphasizes the importance of research evaluation as well as future research directions identifying them as a method to view past progress current issues and future recommendations to effective educational leadership and management. The study looked at key influences in this direction such as educational administration and research leadership, lead and administer education as a humane and ethical endeavour rather than a solitary scientific activity; and analytical resources available to the investigation, evaluate different philosophical and analytical methods in accordance with an agreed set of academic steps for scholars policymakers and practitioners; the potential impact of the maturity of a future generation of researchers on the primacy of educational administration, and current situation. The field of education leadership and administration has made remarkable progress. In future work by scholars on this particular topic the analysis performed in this paper will provide practical responses from intellectuals and their organizations as well as policy makers. Policy makers and education professionals key stakeholders in the fields of information leadership and academic management.